Contextual Teaching and Learning Based on Islamic Religious Education and Its Impact on Praja Religious Behavior - Sarwani Sarwani (International Journal of Nusantara Islam, 2023)
Islamic religious education is not only focused on providing theoretical knowledge, but it should also ensure that the learning experiences of students are always related to current issues in their environment. The Contextual Teaching and Learning (CTL) based model of Islamic religious education establishes a connection between each lesson or topic and real-life situations, aiming to impact the religious beliefs of the students at the Institute of Home Affairs Administration in Jatinangor. This research adopts a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation, while data analysis involves data collection, data presentation, and data processing. The results of this study indicate that the model of Islamic religious education at the Institute of Home Affairs Administration in Jatinangor can be divided into two important parts: Islamic religious education learning in accordance with the national curriculum conducted during classroom hours, and Islamic education and guidance provided by extracurricular units outside of classroom hours as local content.